A rapid screening procedure for cholesterol and dehydrocholesterol by electrospray ionization tandem mass spectrometry - D.W. Johnson; H.J. ten Brink; C. Jakobs (Journal of Lipid Research, 2001)
The mono-(dimethylaminoethyl) succinyl (MDMAES) ester is a new derivative for rapid, mild, and sensitive electrospray ionization tandem mass spectrometry (ESI-MS/MS) analysis of cholesterol and dehydrocholesterol. It is an order of magnitude more sensitive than the previous most practical alternative, the N-methylpyridyl ether derivative. The MDMAES derivative was used to develop a rapid screening procedure for the biochemical diagnosis of Smith-Lemli-Opitz syndrome (SLOS) by measuring the dehydrocholesterol/cholesterol ratio in plasma (5 μl) and plasma spotted onto filter paper. Details of the synthesis of [25,26,26,26,27,27,27-2H7]-7-dehydrocholesterol, used as a standard for quantitation, are included. The measurement of total sterols as MDMAES esters, after base hydrolysis of plasma, afforded a dehydrocholesterol/cholesterol ratio of 0.05–2.95 for SLOS patient samples (n = 5) compared with 0.001–0.003 for normal adult controls (n = 20).Direct hexane extraction of plasma without base hydrolysis enabled the measurement of free sterols with a total sample analysis time of <1 h. The free dehydrocholesterol/cholesterol ratio was 0.10–4.47 for SLOS patient samples (n = 5) and 0.003–0.011 for normal adult controls (n = 20).